THE ROLE OF ENTREPRENEURSHIP AND SMALL-TO-MEDIUM BUSINESS REPRESENTATIVES IN SOCIAL PROTECTION IN SURKHONDARYA REGION (2016–2025) (World Bulletin of Social Sciences, 2026)
This article analyzes the role of entrepreneurship and small-to-medium business entities in the social protection system in Surkhondarya region during 2016–2025. It examines the development of the sponsorship movement, the types of material and moral assistance provided by sponsors, and their impact on socially vulnerable groups. In addition, the study explores the activity of entrepreneurs in ensuring social protection, the effectiveness of the sponsorship system, and existing challenges. The research results indicate that the expansion of entrepreneurial activity and sponsorship assistance in Surkhondarya region played a significant role in supporting low-income segments of the population.